King Alfonso VIII of Castile : Government, Family, and War - Lincoln, Kyle C.; Smith, Damian J.; Gómez, Miguel, 1975- (Book collections on Project MUSE., 2019)
"King Alfonso VIII of Castile: Government, Family and War brings together a diverse group of scholars whose work concerns the reign of Alfonso VIII (1158-1215). This was a critical period in the history of the Iberian peninsula, when the conflict between the Christian north and the Moroccan empire of the Almohads was at its most intense, while the political divisions between the five Christian kingdoms reached their high-water mark. From his troubled ascension as a child to his victory at Las Navas de Tolosa near the end of his fifty-seven-year reign, Alfonso VIII and his kingdom were at the epicenter of many of the most dramatic events of the era."--Provided by publisher